1999
DOI: 10.1121/1.424799
|View full text |Cite
|
Sign up to set email alerts
|

Using broadband humpback whale vocalizations to locate nonvocal whales in shallow water

Abstract: In a previous paper [Makris and Cato, J. Acoust. Soc. Am. 96, 3270 (1994)], it was shown that a vocal member of a humpback whale herd can be used as a source of opportunity to locate nonvocal members with a passive towed array. That analysis employed full-field but narrow-band propagation and scattering models to emphasize the high spatial array gains available. In the present paper, full-field simulations are performed to determine the structure of actual broadband humpback whale vocalizations after scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The solution introduced in this paper is conceptually based on both ANI and multi-static active solutions, where the active sources are produced by surrounding foraging sperm whales at greater depths (from 200 m downwards), which vocalize on their way down and at foraging depths (Zimmer et al, 2003), and in reported cases, likely on their way up until a few minutes before surfacing (Jaquet et al, 2001). The full analysis can be found in Delory et al, 2007. A comparable approach was introduced for the humpback whale (Megaptera novaeangliae) off eastern Australia (Makris & Cato, 1994;Makris et al, 1999). In this study, if the solution were to be applied for monitoring purposes, it would be difficult to implement due to the need for near real-time shallow water propagation modelling as humpback whale vocalizations' spectra peaks are at rather low frequencies and as a result happen to be severely altered in the shallow water waveguide.…”
Section: Ambient Noise Imaging To Track Non-vocalising Sperm Whalesmentioning
confidence: 99%
“…The solution introduced in this paper is conceptually based on both ANI and multi-static active solutions, where the active sources are produced by surrounding foraging sperm whales at greater depths (from 200 m downwards), which vocalize on their way down and at foraging depths (Zimmer et al, 2003), and in reported cases, likely on their way up until a few minutes before surfacing (Jaquet et al, 2001). The full analysis can be found in Delory et al, 2007. A comparable approach was introduced for the humpback whale (Megaptera novaeangliae) off eastern Australia (Makris & Cato, 1994;Makris et al, 1999). In this study, if the solution were to be applied for monitoring purposes, it would be difficult to implement due to the need for near real-time shallow water propagation modelling as humpback whale vocalizations' spectra peaks are at rather low frequencies and as a result happen to be severely altered in the shallow water waveguide.…”
Section: Ambient Noise Imaging To Track Non-vocalising Sperm Whalesmentioning
confidence: 99%
“…Here, feasibility of the possible echolocation function is investigated for large and dense herring aggregations. This differs substantially from the possible ability of baleen whales to detect other whales by active acoustics, which has been previously discussed [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 51%
“…Some researchers have concluded that humpback whales are unable to echolocate using either click trains or tonal sounds. They argue that the echoes generated by such sounds would either be buried in ambient noise/reverberation, or, in contexts where multiple whales are audible, would be lost in the din created by the other vocalizing whales (Au et al, 2001; Makris, Lai, & Cato, 1999). There is clear evidence that at least some sounds produced by humpback whales are prone to generating reverberation (Clark & Ellison, 2004; Mercado, 2016) and that whales often vocalize in locations that are conducive to reverberation (MacKay, Wursig, Bacon, & Selwayn, 2016), suggesting that humpback whales are likely to encounter situations where sounds and echoes produced by other whales may interfere with their ability to detect and localize self-generated echoes (as well as direct signals from other whales).…”
Section: Avoiding Mutual Interferencementioning
confidence: 99%